Rheocasting and Thixocasting: Semi-Solid Casting Technologies - S.THIRU,, CHITRAMBALAM (The Institution of Indian Foundrymen, 2010)
The new trend in the automotive industry and aerospace industry to produce more fuel-efficient automotive vehicles and lightweight engineering components has resulted in the increased use of aluminium and magnesium alloys. Currently, high-pressure die-casting process fulfils the bulk requirement of the automotive industry as well as aerospace industry needs. However, the increasing demands on quality and weight reduction have driven the development of new casting processing technologies. The problems associated with liquid metal high-pressure die-casting have resulted in the increased interest in semi-solid forming processes. Such processes are rheocasting and thixoforming technologies. Rheocasting and thixocasting are potential semi-solid casting techniques. Both are potential foundry processes capable to manufacture lightweight aluminium and magnesium alloy castings. In this article, various aspects on rheocasting technology and thixoforming process are discussed in a simplified manner.